Menyingkap Kodrat Hewani Manusia (Manusia dan Fenomena Kekerasan Massa menurut Elias Canetti) - Wattimena, Reza A.A. (Jurnal Filsafat "WISDOM", 2011)
Despite humans achieve their civilizations in terms of science, philosophy, and technology, they still behave like animal. This is the main argument of Elias Canetti, a Bulgaria-German philosopher, in his magnum opus, namely Crowds and Power. One of animal symptoms of the humans is social conflicts which usually end up in violence, killing, genocide, and other destructive activities. According to Canetti, it occurs because of human nature, namely human abilities to change and combine themselves as masses which have both destructive and creative power. This article discusses the animal nature of human, their ability to change, their tendency to create masses, and relation between masses and power in human life.Keywords: animal nature of human, mass/crowds, power, social conflict